Rekomendasi Pengelolaan Sampah di Kota Sungai Penuh Provinsi Jambi - Asep, Asep; Ansiska, Paisal; Helmi, Dewilna (Program Studi Pendidikan Geografi Universitas Pattimura, 2023)
Environmental management is a step taken as a form of concern in managing waste in a region. Through environmental management, waste management in a particular area can be directed towards desired goals. This research describes the waste management system in Sungai Penuh city and provides recommendations for the management and current state of waste management that has been implemented. This research is described through a mixed method research design. In this case, data is collected through observation and interviews, then analyzed descriptively both qualitatively and quantitatively using the SWOT method. Recommendations for waste management that can be applied in managing waste in Sungai Penuh city include: 1) Providing environmentally friendly waste disposal processing equipment; 2) Enhancing policy efficiency through government collaboration with various stakeholders in waste management; 3) Increasing promotion in comprehensive waste management activities; 4) Conducting ongoing evaluations of field workers in waste management